Language Sounds in Javanese Words: Onomatopoeia, Phonesthemic and Language Logic - Sunarya, Sunarya; Sutono, Agus (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The onomatopoeia discussed in this article is specifically those of the Javanese words, such as the words used in Javanese magazines, Djaka Lodang (DJ), Panjebar Semangat (PS), and Jaya Baya (JB). The described Javanese onomatopoeia words were adjusted to the formation process according to Brandstatter's theory, the onomatopoeic elements can, therefore, be identified. The Javanese onomatopoeic words were analyzed based on qualitative methods, by referring to two techniques of data analysis (Sudaryanto's method), namely the technique of directly comparing the linguistic elements (which Sudaryanto termed agih), and comparing the elements of language with elements outside the language (‘padan’ equivalent), such as utterances or articulators.The onomatopoeic elements in a number of words can be explained based on the formation of root words derived from sound imitation, the type of sound moving objects and its phonestemic aspects, such as the opposition of the size of the sound, and so forth. In this study there are several types of sound imitation, such as sounds of bursting, friction, rounding, rolling, throwing, falling, slapping, opening-closing sounds, coming out- coming in sounds, absorption sounds, etc. This article provides an evidence for the richness of the Javanese words in terms of the sound imitation. Therefore, not only Japanese and Korean are identical to onomatopoeia, the Javanese language spoken in the Island of Java, Indonesia is quite rich with onomatopoeia, especially the secondary one. In addition, the results of this study will hopefully be beneficial for those doing similar studies.